What Are Micro and Small Enterprises Risk-Taking Propensity Levels? - Fauzilah SALLEH; Muhammad Ikhsan SETIAWAN; Muhammad ISMAIL; Ahmad Firdause MD FADZIL; Nor Mazlina ABU BAKAR (Communications of International Proceedings, 2021)
What are micro and small enterprises (MSEs) risk-taking propensity (RTP) levels? Based on the normal distribution, the MSEs were categorised into three levels, namely low, moderate, and high. Using a descriptive analysis, the level of RTP of micro and small enterprises was examined. Data were gathered based on a stratified sample of 260 MSE owners registered with Small and Medium Industries Development Corporation (SME Corp). This study employed the Risk Attitudes Inventory (RAI), developed by Calvert (1993), to determine the level of RTP amidst the selected sample. Results revealed a moderate level of RTP, suggests that MSE owners in Malaysia tend to be risk-averse entrepreneurs, thus hindering their businesses from flourishing. Often entrepreneurship sectors are vulnerable to country inertia and low risk-taking propensity. It was concluded that the level of risk-taking propensity has invariably proven that the latter’s business performance levels are related directly towards risk taking propensity. MSEs owners, who were risk averse, will not excel in their respective business. Future studies regarding MSEs should investigate the demographic factors in line with risk management to describe the significance of weighing in business characteristics. Hence, future research may want to assess if these models are indeed viable in risk management and entrepreneurship domains at varying levels of operation, such as conglomerates.
Keywords: Risk-taking propensity; micro and small enterprises; Malaysia.